Observation of the 02+ and γ bands in 98Ru, and shape coexistence in the Ru isotopes - P.E. Garrett; L. Makhathini; R.A. Bark; T.R. Rodríguez; S. Valbuena; V. Bildstein; T.D. Bucher; C. Burbadge; R. Dubey; T. Faestermann; R. Hertenberger; M. Kamil; et al. (Physics Letters B, 2020)
Excited states in 98Ru were investigated using γ-ray spectroscopy following the β-decay of 98Rh, and via the 100Ru(p,t) reaction. Combining the results from the two experiments, two states were revised to have spin-parity of 4+ and subsequently assigned to the 02+ and “γ” bands, respectively. The observed structures in 98Ru are suggested to be deformed and rotational, rather than spherical and vibrational, and fit well into the systematics of these excitations in the Ru isotopes. The 02+ excitation is suggested as a shape coexisting configuration. This observation eliminates some of the last remaining candidates for nearly harmonic vibrational nuclei in the Z≈50 region. Beyond-mean-field calculations are presented that support shape coexistence throughout the Ru isotopes with N=52–62, and suggest a smooth evolution of the shapes.